Anticholangiocarcinoma activity and toxicity of the Kaempferia galanga Linn. Rhizome ethanolic extract - Asmare Amuamuta; Tullayakorn Plengsuriyakarn; Kesara Na-Bangchang (BMC, 2017)
Abstract Background Cholangiocarcinoma (CCA) is an important public health problem in several tropical and subtropical parts of the world particularly Thailand. Chemotherapy of CCA is largely ineffective and discovery and development of effective alternative drugs is urgently needed. The objective of the study was to confirm the anti-CCA potential as well as toxicity of the crude extract of Kaempferia galangal Linn. (rhizome) both in vitro and in animal models. Methods The ethanolic extract of K. galanga Linn. rhizome, ethyl-p-methoxycinnamate (EPMC) and 5-fluorouracil (5-FU) were evaluated for their cytotoxic activities against CCA cell line (CL-6) using MTT cell proliferation assay. Acute and subacute toxicity of the extract were evaluated in ICR (Imprinting Control Region) mice according to the OECD (International Organization for Economic Co-operation and Development) Guideline. Anti-CCA activity was evaluated in CCA- xenografted nude mice. Results Results of cytotoxicity test showed moderate activity of the extract and EPMC with median (95% confidence interval: 95% CI) 50% inhibitory concentration (IC50) of 64.2 (57.76-72.11) and 49.19 (48.16-52.29) μg/ml, respectively. The IC50 of 5-FU was 107.1 (103.53-109.64) μg/ml. The selectivity index (SI) values for the extract, EPMC and 5-FU against human normal cell line (OUMS) and cancer cell line (CL-6) were 2.2, 2.09 and 1.31, respectively. Toxicity testing revealed no overt toxic effect up to the maximum single oral dose of 5000 mg/kg body weight and up to daily dose of 1000 mg/kg body weight for 30 days. The extract at the maximum tolerated dose level of 1000 mg/kg body weight for 30 days exhibited promising anti-CCA activity in CL6-xenografted nude mice as determined by inhibitory activity on tumor growth (58.41%) and lung metastasis (33.3%), as well as prolongation of survival time (62 days). Conclusion The K. galangal Linn. rhizome extract and its bioactive compound EPMC exhibited moderate cytotoxic activity against human CCA tumor (CL-6) cell line. Results of toxicity testing suggest that the extract was well tolerated up to the maximum single oral dose of 5000 mg/kg body weight and daily dose of 1000 mg/kg body weight for 30 days. The extract exhibited promising anti-CCA activity in CL6-xenografed nude mice as determined by significant inhibitory activity on tumor growth and lung metastasis, as well as prolongation of survival time.